CONFLICT OF INTEREST IN GREEN OPEN SPACE PLANNING IN DENPASAR CITY - Mudra, I Ketut; Siwalatri, Ni Ketut Ayu (International Journal of Engineering and Emerging Technology, 2020)
This research is a response to the regional regulations high intensity violations phenomenon in governing the green open space in Denpasar City. The emergence of this phenomenon as a consequence of a regional regulation core, which is policy taken by the government as a result of synergy, compromise or even competition -in this research called as conflict- between ideas, theories, ideologies and interests. These various interests are the research’s main focus to aim the conflict of interest better understanding in open planning green space of Denpasar City, as part of public policy oriented to the relationship of the planning and development systems of the city. This research is designed using qualitative approach with interpretive method. Problems are examined through three elements of research, namely: (1) green open space in the context of spatial planning and formation; (2) interests involved in green open space planning; and (3) the influence of various interests on the existence of green open space. The findings of the study are that in the context of regional spatial planning, the emergence of violations phenomenon of regional regulations regarding green open spaces in the Denpasar City occurs because of three main conflicts, based on: (1) economic conflict; (2) political conflict; and (3) cultural conflicts. These three main conflicts then trigger the emergence of land use conflicts that threaten the existence of green open spaces in Denpasar City.